VIOLENT BEHAVIOUR DURING SPORTS EVENT OR PUBLIC GATHERING -DISSCUTABLE QUESTIONS IN DOCTRINE AND COURT PRACTICE- - Марјановић, Ђорђе (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In the Criminal Code of the Republic of Serbia, the Serbian lawmaker prescribed the crime of violent behavior during sports events or other public gatherings in the group of criminal offenses against public peace and order. The subject of this work research, which the author analyzes for the purpose of clarifying all perceived dilemmas in the doctrine and domestic judicial practice. In the first part of the paper, the author points out that there was a disagreement between criminal law doctrine and court practice regarding the issue of the place of execution of the crime, as well as the possibility of athletes and other mandatory participants of the sports event being its perpetrators. The author analyzes the emergent forms of the act as well as the dilemmas in their interpretation, showing a large number of unpublished court judgments made in the past ten years in which the defendants were athletes. In the second part of the paper, the author points to the challenge faced by the subjects of the application of norms when distinguishing between the criminal offense of violent behavior at a sports event and the misdemeanors provided for in the Law on Prevention of Violence and Misbehavior at Sports Events. The author points out that the distinction is important especially if the perpetrators are professional athletes, sports experts and experts in the field of sports, and in terms of possible labor law consequences if a criminal offense was committed and not a misdemeanor. In the third part of the paper, the author analyzes the position of the article of the Criminal Code in which violent behavior during sports events or other public gatherings is criminalized, and which obligates the courts to impose the security measure of prohibition from attending certain  sports events on the perpetrators of this act at sports events. In this part, the questions of the justification of the mandatory imposition of the measure are analyzed, as well as the validity of the decision to impose the measure on all persons. The author concludes that the perpetrators of the criminal act of violent behavior at sports events or other public gatherings can be athletes, that the legislator should make an effort to specify certain concepts from the legal description of the act, such as the concept of a sports event, that is, in demarcating the actions of committing a criminal act from misdemeanors that can be committed by violent behavior at a sports event, as well as that it is necessary to make the imposition of a security measure prohibition from attending at sports events optional.
Keywords: 1 LLM, Junior Research Assistant, The Institute of Comparative Law Belgrade, ORCID: 0000-0001-5238-7292, e mail: dj.marjanovic@iup.rs, PhD student at the Faculty of Law in Kragujevac. * This paper is a result of the research conducted at the Institute of Comparative Law financed by the Ministry of Science, Technological Development and Innovation of the Republic of Serbia under the Contract on realisation and financing of scientific research of SRO in 2024 registered under no. 451-03-66/2024-03/200049.